Impact of land use changes on waterlogging disasters in the small urban watershed of Hangzhou - Rikun Wen; Liu Yang; Hexian Jin; Hao Tao; Chingaipe N’tani (Journal of Hydrology: Regional Studies)
Study region: The Gongshu District watershed of the Hangzhou section of the Beijing–Hangzhou Grand Canal. Study Focus: Performing parameter calibration of the grid-based surface and subsurface hydrologic analysis (GSSHA) model and using the GSSHA model to simulate the spatial distribution of waterlogging disasters as well as the changes in water and infiltration depth under different rainfall intensities and Land Use/Land Cover (LULC) change in the watershed. By utilizing overlay and statistical analysis methods, this study quantitatively analyzes the impact of LULC on the urban waterlogging disaster risk. New hydrological insights for the region: 1) Using the GSSHA model to simulate waterlogging disasters at the small urban watershed scale was effective. 2) The waterlogging points in a small watershed were mainly distributed in areas with high building density, low forest area, low elevation, and low surface permeability. The most severely flooded points were often very close to the river system. 3) LULC has a significant impact on the spatial distribution of waterlogging points in small urban watersheds: When the forest area increases, the bare land area decreases, the area of land converted from construction land to forest land increases, the depth of waterlogging decreases, and the infiltration depth increases. 4) The responses of waterlogging and infiltration depth to forest cover exhibit spatial variations under the same rainfall intensity. Greater rainfall intensities led to a greater reduction in waterlogging depth between 2020 and 2021.The findings of this study offer valuable insights for land use planning and urban stormwater management in small urban watersheds.